Graphene grown on hBN by MBE and the deposition of hexacontane on hBN - Diez Albar, Juan (2020)
This thesis discusses the growth of graphene on hexagonal boron nitride (hBN) by high temperature molecular beam epitaxy (MBE) with three different carbon sources: a carbon filament, an atomic carbon source consisting of a thin Ta cylinder and an e-beam source. The flakes were transferred into sapphire wafers previously to graphene growth in order to serve as a refractory support. Graphene layers grown with the different sources present common features but also significant differences which are discussed.